Pengaruh Pertumbuhan Ekonomi, Rata-rata Lama Sekolah, dan Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan di Provinsi Kalimantan Selatan - Sephia, Sephia; Chandriyanti, Ika (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research was conducted focusing on the influence of economic growth variables, the average length of schooling, and the open unemployment rate to determine the level of poverty in South Kalimantan. Using secondary data quantitave research with the number of periods 2009-2021 using the multiple liniear regression method. Based on the results of the study it can be concluded that the variable economic growth has a positive but not significant effect on the level of poverty. RLS has a significant negative effect on the level of poverty. But for TPT it has a significant effect on the level of poverty.